Factors in HIV Prevention - Karki, Tej Bahadur (Journal of Advanced Academic Research, 2015)
Objectives: The main objective of this study is to identify the factors in HIV prevention. Methodology: A descriptive and analytical research design was adopted among 404 respondents. Simple random sampling technique was used to select the respondents from different groups. The Study was conducted in Kathmandu valley. Result: A significant association exists between the awareness raising activities, mandatory blood testing of suspected people, isolating PLHIV from society, addressing the problem of unemployment, improving individual risk behaviour, managing separate red-light area, and stopping stigma and discrimination with HIV risk reduction. Conclusion: Individual people should be more responsible for improving their risk behaviour. Besides that, the society should be amenable to reduce the social taboo about HIV and AIDS and the government should address the problem of unemployment and manage the sex-trade. Journal of Advanced Academic Research Vol.1(1) 2014: 1-8